Perjumpaan dengan Yang Lain: Refleksi Filosofis terhadap Film “Hotel Rwanda” dari perspektif Etika menurut Emmanuel Levinas - Hizkia Fredo Valerian (Jurnal Ledalero, 2021)
This article presents a philosophical reflection on the story of Hotel Rwanda’s film from the Ethic’s perspective of Emmanuel Levinas. Hotel Rwanda’s Film tells a story about the conflict between two of Rwanda’s native tribes, Hutu and Tutsi, that highlighting violence and genocide as the impact of the racial discrimination paradigm. By analyzing some events that were pictures from the film, I saw that two interesting ideas to reflect by Levinas’ Ethic perspective. First, about the dangerous tendency of totality by stigmatizing other people by ideas. And the second is the philosophical idea regards to the meaning of encountering the face of the other, as the basis of responsibility to the other man. In that way, Hotel Rwanda’s film can be presenting a relevant illustration for some core on Levinas’ thought that focusing on the ethical problem concerning justice and humanityKeywords: Hutu, Tutsi, Genocide, The Face, The other, Ethics.